Adaptive RSU re-routing under delay constraint in multi-hop vehicular networks. (2016) - Wang, Kuo-Lung; Wang, Tsan-Pin; Tseng, Chien-Chao
Vehicular wireless networks (VWNs) offer wireless multi-hop communications between vehicles and roadside units (RSUs). A multi-hop wireless network with carry-and-forward routing may suffer from longer delay in packet delivery. However, the applications may demand stringent delay requirement in multi-hop VWNs. Therefore, this paper proposes an adaptive RSU re-routing strategy to alter the current associated RSU to the best RSU under delay or throughput constraints for applications in multi-hop VWNs. Performance results show that the proposed strategy is able to adaptively select a suitable packet size for the trade-off between delay and throughput to satisfy the diverse requirements of applications in multi-hop VWNs.